THE INFLUENCE OF FOOD QUALITY, SERVICE QUALITY, AND PRICE ON CUSTOMER SATISFACTION AT PONDOK TELAGA IKAN - Arifin Fu (Journal of Accounting and Management Innovation, 2023)
A key factor in ensuring a business's long-term viability is customer satisfaction. Customer satisfaction offers information on the business team's performance, whether it is positive or negative. The Pondok Telaga Ikan restaurant is being used as the research object in this paper. The sales data from Pondok Telaga Ikan used in this paper as the study object show a declining revenue, which suggests that the company is unable to sustain its level of customer satisfaction. The purpose of this research is to examine how customer satisfaction at Pondok Telaga Ikan is influenced by the quality of the food, the service quality and price. Purposive sampling, which involved 96 participants, was the method utilized in this study. The data are analyzed using the multiple linear regression method. All hypotheses proposed in this research are accepted. The result of the research shows that food quality has partial influence on customer satisfaction but not significant; service quality has partial influence on customer satisfaction significantly; price has partial influence on customer satisfaction significantly; and food quality, service quality, and price have simultaneous influence on customer satisfaction significantly. It is recommended that Pondok Telaga Ikan improve their food quality by improving kitchen quality control, doing food panel test, and avoid using overkept materials. In terms of service quality, the restaurant could implement proper trainings, and keeping good quality of tangible items served to the customers. In terms of price, the restaurant could analyze the market price and strategically set the price by implement a promotion be it happy hour dining, discount payment with cards, or vouchers so that customers could come back to the restaurant again.